Origins of chromosome instability unveiled by coupled imaging and genomics - Cosenza, Marco R.; Gaiatto, Alice; Erarslan-Uysal, Büşra; Andrades, Álvaro; Sautter, Nina Luisa; Simunovic, Marina; Jendrusch, Michael; Zumalave, Sonia; Rausch, Tobias; Halavatyi, Aliaksandr; Geissen, Eva-Maria; Eigenmann, Joshua Lucas; et al. (Nature, 2025)
Somatic chromosome instability results in widespread structural and numerical chromosomal abnormalities (CAs) during cancer evolution1-3. Although CAs have been linked to mitotic errors resulting in the emergence of nuclear atypia4-7, the underlying processes and rates of spontaneous CA formation in human cells are underexplored. Here we introduce machine-learning-assisted genomics and imaging convergence (MAGIC)—an autonomously operated platform that integrates live-cell imaging of micronucleated cells, machine learning on-the-fly and single-cell genomics to systematically investigate CA formation. Applying MAGIC to near-diploid, non-transformed cell lines, we track de novo CAs over successive cell cycles, highlighting the common role of dicentric chromosomes as initiating events. We determine the baseline CA mutation rate, which approximately doubles in TP53-deficient cells, and observe that chromosome losses arise more frequently than gains. The targeted induction of DNA double-strand breaks along chromosome arms triggers distinct CA processes, revealing stable isochromosomes, coordinated segregation and amplification of isoacentric segments in multiples of two, as well as complex CA outcomes, influenced by the chromosomal break location. Our data contrast de novo CA spectra from somatic mutational landscapes after selection occurred. The experimentation enabled by MAGIC advances the dissection of DNA rearrangement processes, shedding light on fundamental determinants of chromosomal instability.
Veröffentlicht: 29. Oktober 2025
Gesehen am 05.12.2025